2016
DOI: 10.1113/jp272472
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training‐induced changes in integrated myofibrillar protein synthesis are related to hypertrophy only after attenuation of muscle damage

Abstract: Key pointsr Skeletal muscle hypertrophy is one of the main outcomes from resistance training (RT), but how it is modulated throughout training is still unknown.r We show that changes in myofibrillar protein synthesis (MyoPS) after an initial resistance exercise (RE) bout in the first week of RT (T1) were greater than those seen post-RE at the third (T2) and tenth week (T3) of RT, with values being similar at T2 and T3.r Muscle damage (Z-band streaming) was the highest during post-RE recovery at T1, lower at T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
272
7
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(328 citation statements)
references
References 54 publications
22
272
7
13
Order By: Relevance
“…Throughout the exercise training, protein turnover in the post-absorptive state could be a time frame that characterizes high responders to RET through maintenance of protein mass and/or a limiting of muscle loss in the fasted state. Although our study design is unable to define the precise role and time course of the post-absorptive state during RET on muscle hypertrophy, it is clear that this period is important for muscle hypertrophy as several elegant reports have demonstrated (Brook et al 2015; Damas et al 2016). Until recently, the hours following exercise have received the most focus regarding the accrual of new proteins supporting muscle hypertrophy (Mitchell et al 2014).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Throughout the exercise training, protein turnover in the post-absorptive state could be a time frame that characterizes high responders to RET through maintenance of protein mass and/or a limiting of muscle loss in the fasted state. Although our study design is unable to define the precise role and time course of the post-absorptive state during RET on muscle hypertrophy, it is clear that this period is important for muscle hypertrophy as several elegant reports have demonstrated (Brook et al 2015; Damas et al 2016). Until recently, the hours following exercise have received the most focus regarding the accrual of new proteins supporting muscle hypertrophy (Mitchell et al 2014).…”
Section: Discussionmentioning
confidence: 91%
“…In particular, after a period of RET, individuals experience a shorter duration of the acute elevation of MPS following a bout of RE (Damas et al 2015), and a higher rate of basal post-absorptive MPS compared to pre-training levels (Damas et al 2015). Therefore, the adaptation of muscle protein turnover throughout chronic RET may be an important contributor to muscle hypertrophy as more recent studies are starting to reveal (Brook et al 2015; Damas et al 2016). However, the role of muscle protein turnover, specifically in the basal post-absorptive state, during resistance exercise-induced muscle hypertrophy is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Forexample, Mitchell et al reported no correlation between the myofibrillar protein synthesis (MyoPS) response 1–6 h after an initial resistance exercise bout and the magnitude of long-term, RT-induced muscle hypertrophy (Mitchell et al 2014). In an interesting subsequent study, Damas et al (2016) confirmed no relationship between the 24–48 h MyoPS response and eventual myofiber hypertrophy when studying MyoPS during the first week of training; however, strong correlations were noted when MyoPS was quantified in response to exercise during weeks 3 and 10 of a 10-week RT program. The investigators’ assessments of muscle damage suggest that the week-1 MyoPS response was driven largely by damage/repair, whereas the later responses after a few weeks of training were more reflective of anabolism supporting myofiber hypertrophy (Damas et al 2016).…”
Section: Ribosomal Function and Biogenesismentioning
confidence: 89%
“…In an interesting subsequent study, Damas et al (2016) confirmed no relationship between the 24–48 h MyoPS response and eventual myofiber hypertrophy when studying MyoPS during the first week of training; however, strong correlations were noted when MyoPS was quantified in response to exercise during weeks 3 and 10 of a 10-week RT program. The investigators’ assessments of muscle damage suggest that the week-1 MyoPS response was driven largely by damage/repair, whereas the later responses after a few weeks of training were more reflective of anabolism supporting myofiber hypertrophy (Damas et al 2016). Thus, much like the magnitude of myofiber hypertrophy (Bamman et al 2007), the acute muscle protein synthesis response to RT is variable between individuals and the relationship between the two appears to strengthen as training progresses.…”
Section: Ribosomal Function and Biogenesismentioning
confidence: 89%
“…To determine whether the acute resistance exercise induction of p70s6k activity differed between placebo and long-chain n–3 PUFA groups, p70s6k activity was measured before and 2 h after a training session in the last week of the intervention. The last week of training was chosen because the incorporation of long-chain n–3 PUFAs would be maximized at this point and to remove any of the contribution from the acute muscle-damage responses when beginning exercise training (24). …”
Section: Methodsmentioning
confidence: 99%